2010
DOI: 10.1111/j.1750-3841.2010.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Acids in Combination with Sodium Dodecyl Sulfate Caused Quality Deterioration of Fresh‐Cut Iceberg Lettuce during Storage in Modified Atmosphere Package

Abstract: Recent studies showed that sodium acid sulfate (SAS) and levulinic acid (LA) in combination with sodium dodecyl sulfate (SDS) was effective in inactivating human pathogens on Romaine lettuce. The present study investigated the effects of LA and SAS in combination with SDS (as compared with citric acid and chlorine) on the inactivation of E. coli O157:H7 and sensory quality of fresh-cut Iceberg lettuce in modified atmosphere packages during storage at 4 °C. Results showed that LA (0.5% to 3%) and SAS (0.25% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Similar to other studies that showed significant improvements in microbial efficacy with surfactants (11,18,32), the inactivation of L. innocua suspended in solution by LA, PAA, and LA-PAA was increased by 3.0, 1.8, and 1.4 log, respectively. In the case of L. innocua and E. coli K-12 that were attached to romaine and spinach leaves, the average improvement in the antimicrobial activities of LA-PAA with the addition of SLS was from 0.26 to 0.90 log.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to other studies that showed significant improvements in microbial efficacy with surfactants (11,18,32), the inactivation of L. innocua suspended in solution by LA, PAA, and LA-PAA was increased by 3.0, 1.8, and 1.4 log, respectively. In the case of L. innocua and E. coli K-12 that were attached to romaine and spinach leaves, the average improvement in the antimicrobial activities of LA-PAA with the addition of SLS was from 0.26 to 0.90 log.…”
Section: Discussionsupporting
confidence: 84%
“…These testing parameters are normal commercial processing conditions for leafy greens; thus, the results are valid and applicable for commercial scale-up. Previous works on other sanitizers were performed at higher temperatures (20 to 25uC) and longer dwell times (1 to 10 min) (11,17,20,24,30,32), which did not simulate commercial processing conditions. LA-PAA demonstrated significant enhancement in reducing microorganisms that were suspended in wash water and attached to surfaces of the leaves, when compared with CW, LA, and PAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan and group (2009) found fungal reductions after sanitizing melons with peroxyacetic acid at 80 ppm, but noted sensory reductions of aroma and appearance. These same effects in melons have been seen in other produce types with losses in color and texture associated with application of acids and hydrogen peroxide (Fonesca and Rushing 2006;Guan et al 2010;Alexandre et al 2012a,b;Lignou et al 2014). Silveira et al (2008) reported that the firmness of the "Galia" melons over a 10 day shelf life decreased significantly after the application of chlorine dioxide at 3 mg/L, peracetic acid at 80 mg/L, hydrogen peroxide at 50 mg/L and nisin at 250 mg/L.…”
Section: Introductionmentioning
confidence: 61%
“…These same effects in melons have been seen in other produce types with losses in color and texture associated with application of acids and hydrogen peroxide (Fonesca and Rushing ; Guan et al . ; Alexandre et al . ; Lignou et al .…”
Section: Introductionmentioning
confidence: 99%